'No-one visits me anymore': Low Emission Zones and social exclusion via sustainable transport policy. Issue 6 (2nd November 2022) - De Vrij, Eva; Vanoutrive, Thomas
ABSTRACT: For many years, the literature has pointed to the difficulties with the development of transport policy measures which meet both social and environmental policy objectives. Low Emission Zones (LEZ) offer an interesting example of measures that aim to decrease traffic-related air pollution, but which might have significant social effects by reducing the mobility of vulnerable, car-dependent groups. The Antwerp LEZ (Belgium) is used as a case. The assumptions and views in policy documents were compared with the experiences of some affected persons. The research challenges the assumption that only households with a non-compliant vehicle living in the LEZ are impacted by the measure since the LEZ may have a social impact well beyond the delimited zone. Some people with their residence in the LEZ expressed the feeling that they put a burden on friends and relatives from outside the zone who want to visit them. Furthermore, the LEZ affects low-income car owners with an older, damage-prone vehicle that is allowed to enter the zone, by making replacement vehicles less affordable. In general, the case reveals how the views and experiences of those most likely affected by the policy measure are not fully taken into account.